(3VhA GdTgGH aj GdMce hGdCeKGd hGdBOGHs - (3eMeO Hf SdGeI Hf LYaQ Hf Ydj Hf Mcehf GdbVGYj , TgGH GdOjf CHh YHO Gddg,J (B454 (3g` s
(3ChdgG (B:s
(3ef de JZf HGdbQBf adjS efG Ci ef de jSJZf gh hjbJHS ef fhQg hdG jQjO Hg GdZfGA hJQLjY GdUhJ s
(3BNQgG (B:s
(3hbdH dG jNTY hGdbdH GdPi dG jNTY cGdUNQI GdJi dGJdjf dGi EYJHGQ HgG s
(3GdfSNI HgG MhGTs
(3fSNI ecQQI ef GdeNWhW Qbe (B550s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B42 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B71s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1067s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs